Collective Action in Tourism Village Development: A Case Study of Sade Village, Lombok - Annisa Husnul Latifah; Vera Inne Juni Simamora; Gladys Giandi Zahra; Ani Yanah (Ilomata International Journal of Social Science, 2026)
This study examines the dynamics of collective community participation in Sade Village, one of the recognized tourism villages in Central Lombok. Despite its long-standing status as a tourist destination, Sade’s progress toward achieving Desa Mandiri remains hindered by limited collective involvement. This condition raises questions about the community’s role in advancing sustainable tourism. To explore this issue, the research investigates residents’ perceptions of tourism as a shared good, the motivations that drive participation, and the barriers that restrict effective collective action. A qualitative case study was conducted through in-depth interviews and participatory observations with residents and key stakeholders during a three-day field visit in June 2025. The data were analyzed thematically using the Miles and Huberman framework, with credibility strengthened through triangulation, expert review, and inter-coder reliability checks. The findings reveal that while residents recognize tourism as beneficial for the community, their participation remains limited. Material incentives, particularly financial benefits that support daily needs, serve as the strongest motivators, complemented by solidary incentives expressed in communal bonds and cultural preservation. However, these drivers seldom translate into coordinated action due to a passive participation mindset, limited awareness of innovation, and the absence of formal organizational structures. The study concludes that low participation in Sade Village reflects cultural and structural constraints rather than disinterest, enriching CAT’s propositions on institutional emergence and free-rider dynamics. It recommends demonstration-based approaches, selective financial incentives, and formal tourism institutions, linked to national programs such as ADWI, to foster sustainable, community-led development in other villages.